Application of qiyas of profession zakat in zakat management organizations (OPZ) in Indonesia - Nur Hasan (Department of Islamic Economic, Faculty of Economic and Business, Nahdlatul Ulama Islamic University (UNISNU) Jepara, Indonesia, 2022)
This study aims to determine the application of professional zakat calculations in zakat management organizations (OPZ) in Indonesia. This type of research is a qualitative case study and in exploring primary data through interviews with OPZ managers and observations on the mechanism for calculating professional zakat and secondary data in the form of documentation through information in the form of pamphlets and OPZ websites which are officially recognized by the state and published in the Information Management and Documentation Officer (PPID). ) National Amil Zakat Agency as many as 87 OPZ. The results showed that of the 87 official OPZ, 38 did not specifically explain the mechanism for calculating professional zakat, 37 OPZ used one of the qiyas in determining the calculation of professional zakat, namely gold qiyas, commercial qiyas and sabah qiyas and as many as 12 OPZ were inaccessible. In the implementation of calculations based on qiyas by several OPZ, some still have inconsistencies between the implementation of the chosen qiyas law and the implementation of calculations, both the explanation of the calculations listed in the brochure or website as well as the calculation calculator application.